2012
DOI: 10.1111/j.1748-1716.2012.02404.x
|View full text |Cite
|
Sign up to set email alerts
|

Sprint exercise enhances skeletal muscle p70S6k phosphorylation and more so in women than in men

Abstract: It is concluded that repeated 30-s all-out bouts of sprint exercise separated by 20 min of rest increases Akt/mTOR signalling in skeletal muscle. Secondly, signalling downstream of mTOR was stronger in women than in men after sprint exercise indicated by the increased phosphorylation of p70S6k.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 50 publications
(76 reference statements)
3
30
0
Order By: Relevance
“…Sprint exercise increases the phosphorylation of mTOR and p70S6k in the skeletal muscle of healthy men and women (Esbjornsson et al, 2012). High intensity resistance exercise increases protein synthesis in both men and women, which is accompanied by the increased activities of mTOR and p70S6k in leg muscle (Dreyer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sprint exercise increases the phosphorylation of mTOR and p70S6k in the skeletal muscle of healthy men and women (Esbjornsson et al, 2012). High intensity resistance exercise increases protein synthesis in both men and women, which is accompanied by the increased activities of mTOR and p70S6k in leg muscle (Dreyer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[See (Billaut and Bishop, 2009) for review.] In each study, men were ~30% more powerful than women for the knee extensors (Esbjornsson et al, 2006, Billaut and Smith, 2009, Esbjornsson et al, 2012). The difference in decline in power between men and women with multiple high intensity sprints of short duration was associated with the initial power (Billaut and Bishop, 2012).…”
Section: Sex Differences In Muscle Fatigue Are Task Specificmentioning
confidence: 94%
“…Although the relative reduction in power is not always significantly different between men and women [e.g. (Esbjornsson et al, 2006, Esbjornsson et al, 2012, Smith and Billaut, 2012)], several of these studies have revealed sex differences in muscle and whole body metabolism that would likely have functional consequences for multiple sprint exercise of longer durations than several minutes. One functional consequence is that while men exert greater absolute power and speed than women, women recover more quickly than men (Laurent et al, 2010).…”
Section: Sex Differences In Muscle Fatigue Are Task Specificmentioning
confidence: 99%
See 2 more Smart Citations